(untitled) (Revista de Artes Marciales Asiáticas, 2016)
This study aimed at examining the benefits and challenges of practicing Taekwondo (TKD) to adolescents in Addis Ababa. In so doing, the study investigated the nature of TKD training, benefits of practicing TKD, and challenges/problems related with practicing TKD. A descriptive concurrent mixed methods research design was used. Accordingly, the quantitative part of the study had 108 TKD adolescent participants while the qualitative part had 12 participants (eight TKD adolescents and four TKD coaches), from four TKD clubs in Addis Ababa. Both one-stage cluster sampling technique and purposive sampling technique were employed to select participants for the quantitative and qualitative parts of the study, respectively. Questionnaires and in-depth interviews were used to collect data from participants. Results of the study indicated: (1) the TKD training provided by the four TKD clubs was more of a modern/sport form of TKD; (2) TKD adolescents and coaches perceived that the benefits of TKD for adolescents are multifaceted, i.e., social benefits, physical benefits, mental benefits, self-defense, addiction avoidance, and other benefits; and (3) though majority (63.6%) of the respondents claimed that they did not face any problem as a result of practicing TKD, the following were identified as major problems that could threaten the wellbeing of TKD adolescents: family-related problems, community-related problems, and competition-related problems. In general, results show that the training of TKD can have a multifaceted positive contribution to adolescents’ wellbeing.